Keep Fit: Marginal Ideas in Contemporary Therapeutic Exercise - Nicholls, D; Jachyra, P; Gibson, BE; Fusco, C; Setchell, J (Taylor & Francis (Routledge), 2018)
Exercise has a long history as a therapeutic modality and has existed, in some form, in all cultures throughout recorded history. In recent years, therapeutic exercise has taken on new significance as a relatively low cost medical intervention designed to improve people’s health and well-being and reduce the downstream effects of comorbidity. Drawing our inspiration from Foucault and Deleuze, we argue that seeing therapeutic exercise as primarily ‘medical’ carries with it consequences – some recognised, others unseen – that are problematic and worthy of consideration. Our focus is on the acts of marginalisation, exile and exclusion implicit in the quotidian practice of therapeutic exercise, and how these acts mediate people’s daily lives. In the paper we explore how therapeutic exercise is being instrumentalised, normalised and constrained, arguing for much greater critical attention towards its putative ‘goodness’ and virtue as a health intervention.
Keywords: Therapeutic exercise; Play; Foucault; Deleuze